Cytotoxic and Antiproliferative Activities of Melia azedarach Leaves Ethanolic Extract on A549 Human Lung Cancer Cells - Irshan, Yusuf; Suparto, Irma H; Sulistiyani, Sulistiyani (Jurnal Jamu Indonesia, 2017)
Melia azedarach (Meliaceae) is known locally as mindi, gringging, renceh, or cakra-cikri is known to have pharmacological properties. The leaves contain flavonoids such as kaempferol and quercetin that have anticancer activity. The objective of this research is to evaluate the potency of Melia azedarach leaves ethanolic extract as anticancer by inhibition of cancer cell proliferation. Cytotoxic effect was analyzed by Brine Shrimp Lethality Test (BSLT) and cell viability (MTT) methods using Chang human normal liver cells and A549 human lung cancer cells. Antiproliferative effect of the extract was analyzed by cell direct calculation method using hemacytometer. The leaves were extracted with ethanol 96% by maceration method. Phytochemical investigation showed that the extract contains flavonoids, alkaloids, tannins, saponins, and steroids. Assay of BSLT showed that crude ethanolic extract of M. azedarach has a cytotoxic effect with LC50 value of 63.98 µg/mL, which is an indication for very potential bioactive compund as anticancer. Consistent with BSLT assay, cell viability (MTT) assay showed that this extract was able to reduce cell viability with IC50 values of 299.22 µg/mL on Chang cells and 130.56 µg/mL on A549 cancer cells. As control, Curcuma zedoaria extract at 75 µg/mL reduced A549 cells viability to 38.8%, which was equivalent to the effect of M. azedarach extract at 50 µg/mL. These data suggest that Melia azedarach extract is potentially more bioactive than Curcuma zedoaria extract. This result is supported by the ability of the extract (5 µg/mL) to inhibit A549 cells proliferation as much as 73.53%.